Risk factors and genetic characteristics of the carriage of hypervirulent and carbapenem-resistant Acinetobacter baumannii among pregnant women - Zheng, Chao; Li, Defeng; Wang, Yinglan; Wang, Lisheng; Huang, Yuting; Yao, Jun (Frontiers in Microbiology, 2024)
Background: Carbapenem-resistant Acinetobacter baumannii (CRAB) and its emerging evolutionary branch toward hypervirulence have been neglected in pregnancy.Methods: From September 2020 to August 2021, an active surveillance culture program encompassed 138 randomly selected pregnant women, with five subjected to sample collection at two different time points. The clinical characterization was explored through statistical analysis. Wholegenome sequencing, a Galleria mellonella infection model, and a global database were used to investigate the genetic characterization, pathogenicity, evolutionary history, and phylogenetic relationships of the isolates.Results: Of the 41 CRAB isolates obtained, they were divided into four Clusters RS and an orphan pattern. Cluster RS 1 (n = 31), with eight complex types in pregnancy, was also the dominant Cluster RS globally, followed by Cluster RS 13 (n =5), identified as hypervirulent KL49 CRAB, exhibiting phylogeographical specificity to Guangdong. A maternal carriage CRAB rate of 26.09% (36/138) was revealed, with half of the isolates representing novel complex types, prominently including CT3071, as the first KL7 isolates identified in Shenzhen. Both KL49 and KL7 isolates were most commonly found in the same participant, suggesting potential intraspecific competition as a possible reason for CRAB infection without carriers during pregnancy. The independent risk factors for carriers were revealed for the first time, including advanced maternal age, gestational diabetes mellitus, and Group B Streptococcus infection.The significant carriage rate and enhanced virulence of CRAB during pregnancy emphasize the imperative for routine surveillance to forestall dissemination within this high-risk group, especially in Guangdong for Cluster RS 13 isolates.